Research Based Learning on Student Learning Outcomes in Statistics Course - Mayang Dintarini; Adi Slamet Kusumawardhana (MEJ (Mathematics Education Journal), 2020)
This study aims to describe the application of research-based learning in statistics courses, and determine its effectiveness on student learning outcomes in statistics. This research was an experimental research with a qualitative quantitative approach. The research design used posttest only design, where there were two classes studied, one experimental class and one control class. The population and sample of this research were University of Muhammadiyah Malang students who were taking Statistics courses. The experimental class was given treatment research-based learning, while the control class was given conventional learning. Then both classes were given a posttest to find out the learning outcomes. Analysis of research data using independent sample T-Test. The effectiveness of the application of Research-Based Learning can be seen by comparing the average final work of experimental and control class students. Based on the data processing with SPSS, the average of the experimental group was better than the control group and showed that Research-based Learning had an impact on the average final grades of experimental class students so that it becomes better than the average control class students.